Building a practical information security program - Andress, Jason; Leary, Mark (Cambridge, MA : Syngress, 2017)
Demonstrates how to resolve immediate tactical needs, transform security needs into strategic goals, and put programs into operation with full lifecycle management.
Chapter 0. Why we need security programs -- chapter 1. Develop an information security strategy -- chapter 2. Integrate security into the organization -- chapter 3. Establish a security organization -- chapter 4. Why information security policies? -- chapter 5. Manage the risks -- chapter 6. Protect the data -- chapter 7. Manage the security of third parties and vendors -- chapter 8. Conduct security awareness and training -- chapter 9. Security compliance management and auditing -- chapter 10. Information security program metrics.
Includes bibliographical references and index.
Keywords: Computer networks -- Security measures; Information storage and retrieval systems -- Security measures; Computer security; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; COMPUTERS -- Security -- General; Computer networks -- Security measures; Computer security; Information storage and retrieval systems -- Security measures; Electronic books